812 Evaluating the Impact of Surgical Subspecialisation on Patient Outcomes Following Adhesional Small Bowel Obstruction. (19th August 2022) - Stienstra, R; Green, L; Brown, L; McLean, R; Crumley, A; Hendry, P
Abstract: Aim: Small bowel obstruction (SBO) is the most common indication for laparotomy in the UK. While general surgeons have become increasingly subspecialised in their elective practice, emergency admissions frequently remain undifferentiated. This study aimed to assess temporal trends in the management of adhesional SBO and explore the influence of subspecialisation. Method: Data was collected for patients admitted acutely with SBO across Northern England between 01/01/02 and 31/12/16, including demographics, co-morbidities and procedures performed. Patients were excluded if a non-adhesional cause was identified and were grouped by the responsible consultant's subspecialty. The primary outcome of interest was 30-day inpatient mortality. Results: 2818 patients were admitted with adhesional SBO during a 15-year period. There was a consistent female preponderance (55.9%), while age and comorbidity increased significantly over time (both p<0.001). The proportion treated conservatively decreased (47.1% vs. 40.4%, p=0.009), as did the time to operation (median 2 vs. 1 day, p<0.001). There was an increased propensity for patients to be managed by gastrointestinal (colorectal & upper gastrointestinal) subspecialists (69.9% vs 51.6%, p<0.001). While a trend towards laparoscopy was evident (p=0.005), particularly amongst gastrointestinal subspecialists, uptake remained limited. Length of stay (p<0.001) and 30-day mortality (p<0.001) have improved over time, with the best outcomes seen in colorectal (2.6%) and vascular subspecialists (2.4%). However, following adjustment for confounding variables, consultant subspecialty was not a predictor of mortality. Conclusions: Outcomes following adhesional SBO have improved despite the increasing burden of age and co-morbidity. While gastrointestinal subspecialists are increasingly responsible for their care, mortality is not influenced by consultant subspecialty.